2013
DOI: 10.1371/journal.ppat.1003579
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Specialization of the Small Interfering RNA Pathway in Response to Virus Infection

Abstract: In Drosophila, post-transcriptional gene silencing occurs when exogenous or endogenous double stranded RNA (dsRNA) is processed into small interfering RNAs (siRNAs) by Dicer-2 (Dcr-2) in association with a dsRNA-binding protein (dsRBP) cofactor called Loquacious (Loqs-PD). siRNAs are then loaded onto Argonaute-2 (Ago2) by the action of Dcr-2 with another dsRBP cofactor called R2D2. Loaded Ago2 executes the destruction of target RNAs that have sequence complementarity to siRNAs. Although Dcr-2, R2D2, and Ago2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(130 citation statements)
references
References 61 publications
7
112
0
7
Order By: Relevance
“…Both insects and plants use RNAi as a primary defense against virus infections. RNAi activity results in distinct populations of overlapping sRNAs derived from the RNAi-targeted viral genomes, and in insects, 21-nt sRNAs represent the primary size class (9,60,61,(96)(97)(98). In our study, the size distribution of sRNAs mapping to the putative viruses had a prominent peak at 21 nt (data not shown), suggesting that these putative viruses may originate from viral infections of D. citri and may be processed by the antiviral RNAi machinery.…”
Section: Discussionmentioning
confidence: 53%
“…Both insects and plants use RNAi as a primary defense against virus infections. RNAi activity results in distinct populations of overlapping sRNAs derived from the RNAi-targeted viral genomes, and in insects, 21-nt sRNAs represent the primary size class (9,60,61,(96)(97)(98). In our study, the size distribution of sRNAs mapping to the putative viruses had a prominent peak at 21 nt (data not shown), suggesting that these putative viruses may originate from viral infections of D. citri and may be processed by the antiviral RNAi machinery.…”
Section: Discussionmentioning
confidence: 53%
“…The four sequence collections were analyzed with WebLogo 3 program (http://weblogo .threeplusone.com/create.cgi) (24). The statistical significance (P Ͻ 0.05) of enriched or depleted bases of the created logos was evaluated with one-proportion Z-tests as previously described (25). For the delineation of the degenerate motif of DVNV DC at the cut site (ˆ) of vsRNAs, only the positions with statistically significantly enriched or depleted bases in the logos of all four sequence collections were selected.…”
Section: Methodsmentioning
confidence: 99%
“…E xperiments in the model organism Drosophila melanogaster have shown that RNA interference (RNAi) plays a major role in antiviral immunity in insects: (i) flies with mutations for the three key genes of the small interfering RNA (siRNA) pathway, Dicer-2, Argonaute 2, and r2d2, show increased sensitivity to infection by RNA and DNA viruses (1-6); (ii) Dicer-2-dependent 21-nucleotide siRNAs of viral origin accumulate in virus-infected flies (1,3,4,(7)(8)(9); (iii) several insect viruses express viral suppressors of RNAi (5,(10)(11)(12). The importance of this pathway in the control of viral infections has been confirmed in other insects, in particular, the vector mosquito genera Aedes and Culex, which transmit important human pathogens such as dengue virus, West Nile virus, and other arthropod-borne viruses (13)(14)(15)(16)(17)(18).…”
Section: Importancementioning
confidence: 99%